Line guided based library system mobile robot - Tan, Yih Hui (2016)
Technology plays an important role in today’s society. A lot of library have been changed from a traditional library to a digital library. Library management system and the campus smart card system that been implemented in the library as book procurement, classifying management, transportation management and book inquiry. With these two systems that been implemented in the library, it only helps its user to identify the location of the book and the availability of the book. Sometime users require a period of time to search for the book. With the advance in technology line following robot, Automated Guided Vehicles and industrial robot is being implement in the industry to increase productivity. In order to overcome this problem, an automated pick and place system for book keeping operation is being developed. The maximum load sustained by the robot arm made using aluminum 6061is analyzed. In this project Arduino Uno was selected as the microcontroller of the robot. GUI was created using Visual Basic and the serial communication is selected as the communication tool between microcontroller and GUI. In order to determine the maximum load which can sustain by the robot arm. The material aluminum 6061 was analyzed by using computer software (SOLIDWORK) which calculates the finite element of linear stress analysis of each mechanical components of robotic arm. From the result, the robot is able to reduce the burden on librarians and reduce the time taken for its user to search for the book